Pull-out behaviour of steel fibres recycled from used tyres - Tlemat, H.; Pilakoutas, Kypros; Neocleous, Costas (My University, 2003)
It is estimated that currently in the UK around 60,000 tonnes of steel are discarded as part of the cord and bead of used tyres. As a result of environmental legislation there is an urgent need to find alternative uses for this steel, which consists of high quality fibres, to avoid disposing it in landfills. Work at the University of Sheffield has recently demonstrated that steel fibre from recycled tyres can be used as reinforcement in concrete. To optimise the use of steel fibres in concrete and to obtain the optimum bond strength without fibre failure, the critical fibre length needs to be determined. This paper presents a study on the bond characteristics of steel fibres from used tyres. The current experimental program investigates the pull-out behaviour of different fibre types by using a double-sided pull-out test method. Single and multi-fibre pull-out set-ups are employed in these experiments. It was found that fibres from recycled used tyres have as good bond characteristics as commercially available steel fibres.
Keywords: Pull-out behaviour; Recycled steel fibres; SFRC; Used tyres